(3TQM GdYHGOGJs - (3HgGA GdOjf GdjYbhHi GdMfHdis; (3GdcdhPGfj , eMahX Hf CMeO Hf GdMSf, CHh GdNWGH,J (B510 (3g` s ((3eMeO Hf CHj efUhQ Hf HNG GdQbi s)
(3ChdgG (B:s
(3HGH GdejGg Ydi KdGKI CbSGe , WghQ hWGgQ , hfLS s
(3BNQgG (B:s
(3Qhi Yf Ydi cQe Gddg hLgg Cfg Mdb QCS GdMSf hde jYQa dg eNGda fLRJ GdYHGOGJ HTQMgG s
(3GdhQbI GdChdi HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdMfHdjs